Numerical Simulation Research on the Irradiation-Thermal-Mechanical Performance Evolution of FCM Fuel - Changbing, Tang; Yuanming, Li; Yongjun, Jiao; Kun, Zhang; Peng, Wang (Frontiers in Energy Research, 2021)
FCM fuel which microencapsulated TRISO particles in SiC matrix is a promising ATF (accident tolerant fuel) candidate fuel designed to replace the traditional pellet-cladding fuel rod. In order to predict the in-pile behavior of FCM fuel accurately and to optimize the design of FCM fuel, it is necessary to establish a numerical simulation method of irradiation-thermal -mechanical coupling behavior of FCM fuel. In this study, the related thermal effects and irradiation effects of FCM fuel and the effect of gap heat transfer are considered. User defined subroutines are compiled respectively, and the above-mentioned correlation effects are introduced into ABAQUS software to establish a numerical simulation method for the irradiation-thermal -mechanical coupling behavior of FCM fuel. Based on the established numerical simulation method, the performance evolution of FCM fuel in the reactor is simulated, and the possible failure modes of FCM fuel in the reactor are analyzed. The research results can provide guidance for the optimization design and performance prediction of FCM fuel.